PROSEDUR PEMERIKSAAN RADIOGRAFI CLAVICULA DENGAN KLINIS FRAKTUR DI RSUD RAA SOEWONDO PATI - Affan Haqqi, Mohamad; Sulaksono , Nanang (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Clavicula examination procedure with clinical fractures in radiology installation RAA Soewondo Pati Hospital was using only Antero Posterior (AP) projection. The purpose of this research is to know the clavicle examination procedure with clinical fractures and find out the reasons for using Antero Posterior (AP) projections. Methods: Type of this research is qualitative research with approach case studies. Data were collected by observation, in-depth interviews, and documentation. This research took place in the radiology installation of RAA Soewondo Pati Hospital. Data analysis was carried out with interactive model three steps, namely data collection, data reduction, data presentation. Results: The results showed the clavicula examination procedure with clinical fractures in radiology installation RAA Soewondo Pati Hospital was using Antero Posterior (AP) projection. Conclusions: The reason for using this projections is because this projections have provided diagnostic anatomy information and its enough to make a the diagnosis. But to show costae 1 and 2 and clavicle appear more clear and not superposition each other should use AP Axial projections.